PERLINDUNGAN HUKUM TERHADAP PRODUSER FILM ATAS PENGUNGKAPAN SUBSTANSI KARYA SINEMATOGRAFI MELALUI PLATFORM DIGITAL - Noviyanti, Ni Kadek Sri; Samsithawrati, Putu Aras (Kertha Negara : Journal Ilmu Hukum, 2025)
This research aims to analyze the legal protection and impacts faced by copyright holders in cinematographic works, particularly film producers, regarding the disclosure of film story details on digital platforms. The digital technology era has brought new challenges to the film industry, especially concerning the phenomenon of spoilers and illegal distribution of film content on digital platforms, which potentially harms copyright holders, especially film producers. This journal article uses a normative legal research method and employs statutory and conceptual approaches. The research results show that: (1) legal protection for copyright holders of cinematographic works, particularly film producers, regarding the disclosure of film story details on digital platforms is regulated in Article 99 of the Copyright Law and Article 32 of the Electronic Information and Transactions Law, covering both preventive and repressive aspects. These laws protect the moral and economic rights of film producers, with clear criminal sanctions; and (2) the legal consequences that may be faced by parties publishing detailed descriptions of cinematographic works on digital platforms can be seen in Article 113 paragraph (4) of the Copyright Law, which stipulates penalties of up to ten years imprisonment and fines of up to four billion Rupiah, or Article 32 in conjunction with Article 48 paragraph (3) which stipulates fines of up to five billion Rupiah for violators. Although freedom of expression is important, excessive disclosure of details that harm the economic interests of film producers may violate the boundaries of fair use